The authorship of Neolissochilus soro (Cypriniformes: Cyprinidae): a correction to Khaironizam et al. (2015) - Scharpf, Christopher (Zootaxa, 2015)
In a meristic, morphometric and distributional study of Neolissochilus from Peninsular Malaysia, Khaironizam et al. (2015) subsumed Lissochilus tweediei Herre in Herre & Myers 1937 and a taxon they called “Tor soro Bishop 1973” into the synonymy of N. soroides (Duncker 1904) based on data collected from museum specimens. However, “Bishop 1973” is not the correct author citation for Tor soro. Instead, Tor (now placed in Neolissochilus) soro was originally described as Barbus soro by Valenciennes in Cuvier & Valenciennes (1842:191). Since “Tor soro Bishop 1973” is not a valid name/author combination, Neolissochilus soro, as treated by Khaironizam et al. (2015), cannot be considered a junior synonym of N. soroides.